eCM 2020
DOI: 10.22203/ecm.v039a04
|View full text |Cite
|
Sign up to set email alerts
|

Link N suppresses interleukin-1β-induced biological effects on human osteoarthritic cartilage

Abstract: Osteoarthritis (OA) is a disease of diarthrodial joints associated with extracellular matrix proteolytic degradation under inflammatory conditions, pain and disability. Currently, there is no therapy to prevent, reverse or modulate the disease course. The present study aimed at evaluating the regenerative potential of Link N (LN) in human OA cartilage in an inflammatory milieu and determining if it could affect pain-related behaviour in a knee OA mouse injury model. Osteo-chondro OA explants and OA chondrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
3
3
0
Order By: Relevance
“…This finding was in an agreement with earlier data (Alaqeel et al, 2020) showing that LN can restore GAG production to healthy control levels in human osteoarthritic cartilage when exposed to IL-1β, an inflammatory cytokine known for its catabolic activities in cartilage and IVD (Masuda and An, 2004;Yang et al, 2015). The strong effect of LN observed in these conditions could be partly explained by the fact that LN inhibits IL-1β signalling pathways (Alaqeel et al, 2020). Interestingly, the study's findings demonstrated that in a degenerative medium, the level of GAG achieved with LN reached similar levels to those observed with TGF-β.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding was in an agreement with earlier data (Alaqeel et al, 2020) showing that LN can restore GAG production to healthy control levels in human osteoarthritic cartilage when exposed to IL-1β, an inflammatory cytokine known for its catabolic activities in cartilage and IVD (Masuda and An, 2004;Yang et al, 2015). The strong effect of LN observed in these conditions could be partly explained by the fact that LN inhibits IL-1β signalling pathways (Alaqeel et al, 2020). Interestingly, the study's findings demonstrated that in a degenerative medium, the level of GAG achieved with LN reached similar levels to those observed with TGF-β.…”
Section: Discussionsupporting
confidence: 94%
“…Data indicated that, under conditions mimicking the degenerative disc environment, LN induced a strong increase in GAG production by NP cells. This finding was in an agreement with earlier data (Alaqeel et al, 2020) showing that LN can restore GAG production to healthy control levels in human osteoarthritic cartilage when exposed to IL-1β, an inflammatory cytokine known for its catabolic activities in cartilage and IVD (Masuda and An, 2004;Yang et al, 2015). The strong effect of LN observed in these conditions could be partly explained by the fact that LN inhibits IL-1β signalling pathways (Alaqeel et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another mechanism by which Link N may be inhibiting the induction of NTs by inflammatory cytokines in IVD cells is by decreasing cytokine signaling pathway. In our unpublished work, human chondrocytes coexposed to IL‐1β and Link N demonstrated a reduced activation of nuclear factor‐κB when compared to chondrocytes treated with IL‐1β alone . Since the IL‐1β signaling pathway is important in mediating NTs upregulation, factors that inhibit IL‐1β receptor signaling (ie, IL‐1 receptor antagonist) may play a role in regulating the pathogenesis of degenerative IVD disease.…”
Section: Discussionmentioning
confidence: 89%
“…Link protein is a glycoprotein that interacts with and connects hyaluronic acid and aggrecan, and thus stabilizes the cartilage ECM. Recent studies have demonstrated that a short N-terminal fragment has anabolic functions, promotes matrix production and decreases the activity of catabolic enzymes, including MMPs, in degenerating intervertebral discs [ 87 ] but also human OA cartilage [ 88 ]. The fragmentation of the perifibrillar proteoglycans decorin, biglycan, lumican and keratocan is elevated in degenerating human meniscus, knee and hip articular cartilages compared with age-matched macroscopically normal and control tissues [ 89 ].…”
Section: The Role Of Proteases and Cytokines In Oamentioning
confidence: 99%